The Self Reflected In Sabrina Jeffries's The Pirate Lord Novel (1998): An Existentialist Approach - Pamungkas, Febrianti Wahyu; , Dr. Phil. Dewi Candraningrum, M.Ed; , Drs. Abdillah Nugroho, M.Hum (2013)
The major problem of this study how is the self reflected in Sabrina Jeffries's The Pirate Lord novel (1998). The study is intended to analyze the novel based on structural elements and to analyze the novel based on the existentialist approach. The object of this study is The Pirate Lord novel by Sabrina Jeffries. The researcher employs the descriptive qualitative as a type of the research. The data source in this research is divided into two types that are primary data and secondary data. Primary data source is The Pirate Lord novel and secondary data source is books or any information related to the practice of self that support the existentialist approach. The method of collecting data is reading the novel. The technique of analyzing data in this research paper is descriptive The result of the study comes to the three following conclusions. First, based on structural element in The Pirate Lord, it shows that character and characterization, setting, plot, point of view, style, and theme are related to each other and form unity. Second, based on existentialist analysis, being, existence before essence, cogito, freedom, anxiety, transcendence of ego, nothingness are reflected in Sara Willis's life. Third, theory of self is the individual characteristic in human's life. It shows that the characteristic by Sara Willis causes the conflict of her life.